2009
DOI: 10.1021/jz900037x
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Carbon Monoxide on Dendrimer-Encapsulated Platinum Nanoparticles: Liquid versus Gas Phase

Abstract: The ability of dendrimer-encapsulated platinum nanoparticles (Pt DENs) to adsorb carbon monoxide was contrasted in the gas versus liquid phases by using in situ infrared absorption spectroscopy. It was found that while only limited, weak, and reversible adsorption is possible in the gas phase, extensive and stronger adsorption occurs in the liquid phase, even when the Pt DENs are dispersed inside of the pores of a high surface-area solid. It is speculated that the dendrimer structure may collapse in the gas ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 28 publications
4
52
0
Order By: Relevance
“…93 It was found that in polar solvents CO adsorbed strongly and extensively to the DEN surface. However, dry DENs exhibited weaker adsorption and lower coverages of CO.…”
Section: 92mentioning
confidence: 99%
“…93 It was found that in polar solvents CO adsorbed strongly and extensively to the DEN surface. However, dry DENs exhibited weaker adsorption and lower coverages of CO.…”
Section: 92mentioning
confidence: 99%
“…These properties also impact the catalytic reactivity of the nanoparticles [42]. A dendrimer templating strategy is very attractive for synthesis of small nanoparticles [43][44][45]. The size of metal nanoparticles synthesized within polyamidoamine (PA-MAM) dendrimers is controlled by the number of functional groups in the dendrimer and the structure of the dendrimer matrix (Fig.…”
Section: Dendrimer-templated Synthesis Of Small (*1 Nm) Metallic Nanomentioning
confidence: 99%
“…The dendrimer also provides a shell that prevents aggregation of the as-grown nanoparticles. By changing the metal ion to dendrimer concentrations ratio, a variety of monometallic and bimetallic nanoparticles in the size range of 1 nm were synthesized with narrow size distribution [43][44][45].…”
Section: Dendrimer-templated Synthesis Of Small (*1 Nm) Metallic Nanomentioning
confidence: 99%
“…[301][302][303] However, it has been established that the use of different capping agents may result in different catalytic performances, [304][305][306] an observation that perhaps offers another possibility to tune selectivity. In liquid phase, the surfactants used in colloidal, micelle, dendrimer, and other self-assembly synthesis may be retained, and the catalysts may be used without the need for further treatment.…”
Section: Discussionmentioning
confidence: 99%